Effects of fiber reinforcements weave patterns on the mechanical properties of hybrid intraply lamina - Husin, Mohd Amirhafizan (2016)
Laminate hybrid composites can be classified into two structure types such as interply and intraply structure. This research focuses on the effect of weave designs on mechanical properties of the single ply or also known as intraply hybrid composite lamina made by vacuum infusion technique. The eighteen (18) specimen of intraply composites lamina were made by kenaf fiber and glass fiber as a reinforcement and unsaturated polyester resin as a matrix with three types composition which were kenaf fiber in warp and weft direction (100 % kenaf), kenaf fiber in warp direction and glass fiber in weft direction (WK – WG), and lastly glass fiber in warp direction and kenaf fiber in weft direction (WG – WK) in various weave designs which were plain, twill, satin, basket, mock leno and leno weave. By using different weave designs and different materials in warp and weft direction had significantly affect the mechanical strength. The lamina intraply composites from WG – WK had significantly highest tensile strength and better mechanical properties which were plain, twill, satin, basket, mock leno and leno weave increased about 61.1 %, 93.9 %, 101.0 %, 95.8 %, 145.7 % and 49.1 % respectively compared pure kenaf. The most effectiveness of weave design for lamina composite were twill weave and satin weave in WG – WK with tensile strength 93.85 MPa and 97.35 MPa respectively. Lastly the leno weave was found to be not effective weave design for lamina intraply composite. This is due to the structure and the fiber content of leno weave.